1998
DOI: 10.1093/oxfordjournals.aje.a009564
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual Transmission of Human Immunodeficiency Virus: Variability of Infectivity throughout the Course of Infection

Abstract: Although individuals infected with human immunodeficiency virus (HIV) seem to be more infectious in the late stages of HIV infection and possibly also during the seroconversion period, most estimates of per-sexual-contact infectivity have been obtained without allowing for variability over the course of infection. In this analysis, a probabilistic model was fitted to data from a European study carried out between 1987 and 1992 that involved 499 (359 males and 140 females) HIV-infected subjects (index cases) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
153
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(163 citation statements)
references
References 24 publications
6
153
0
2
Order By: Relevance
“…Men were five times more commonly affected than women. The most common age group affected was the 31-40 years; this is consistent with the findings of Leynaert et al [17] and Kumar [18] et al who observed the highest incidence of HIV in the late twenties and thirties.…”
Section: Age and Sex Incidencesupporting
confidence: 90%
“…Men were five times more commonly affected than women. The most common age group affected was the 31-40 years; this is consistent with the findings of Leynaert et al [17] and Kumar [18] et al who observed the highest incidence of HIV in the late twenties and thirties.…”
Section: Age and Sex Incidencesupporting
confidence: 90%
“…Retrospective cohort studies of patients infected by sexual contact (89) or blood transfusion (S75) have confirmed significantly increased risk of infection among those exposed to index cases with acute or recent infection. Recently, Wawer and colleagues (80) examined the link between acute disease stage and transmission in a remarkable study of couples in Rakai, Uganda, who were screened for HIV infection and followed as part of an STD treatment trial.…”
Section: Acute Hiv and Clinical Implications A Unique Role For Acute mentioning
confidence: 99%
“…11 Within the sexual transmission category, anal, oral, and vaginal intercourse bring different levels of risk. 12 An anatomical difference is that semen is retained in the posterior vagina in much greater volume than vaginal fluid is retained postcoitus on the penis. Furthermore, since plasma HIV-1 RNA levels have been reported to be higher in HIV-1-infected men than in HIV-1-infected women 13,14 and the diversity of transmitted viral variants may be greater in women than men, 15 the correlates of female-to-male (FTM) and male-tofemale (MTF) transmission may differ for penile-vaginal intercourse.…”
Section: Introductionmentioning
confidence: 99%